Prediction of Posttransplantation Recurrence of Hepatocellular Carcinoma Using Metabolic and Volumetric Indices of18F-FDG PET/CT - Yong‐Il Kim; Jin Chul Paeng; Gi Jeong Cheon; Kyung‐Suk Suh; Dong Soo Lee; June-Key Chung; Keon Wook Kang (2016)
18F-FDG PET is an effective method of predicting recurrence of hepatocellular carcinoma (HCC) after liver transplantation. We compared recently introduced metabolic and volumetric 18F-FDG PET/CT indices with the current clinicopathologic predictors for ability to predict recurrence. Methods: In total, 110 HCC patients who underwent 18F-FDG PET and liver transplantation were enrolled. On PET, SUVs and tumor-to-background ratios (TBRs) were measured as metabolic activity indices. Various metabolic tumor volumes and uptake-volume products (UVP) were also measured as volumetric indices. The ability of these indices and other clinicopathologic factors to predict recurrence was compared. Results: All metabolic and volumetric indices were significant for recurrence prediction on receiver-operating-characteristic curve analyses (P < 0.001). On univariate survival analyses, all PET indices—as well as tumor size, tumor number, the Milan criteria, tumor grade, vascular invasion, and T-stage—were significant factors. However, on multivariate analyses, tumor size, tumor grade, maximum TBR, and UVP calculated by inferior vena cava activity were significant factors (P = 0.004, 0.014, 0.009, and 0.021, respectively). When the Milan criteria and PET factors were included in the multivariate analysis, the Milan criteria (P = 0.029), maximum TBR (P < 0.001), and UVP (P = 0.016) were significant. Conclusion: Volumetric and metabolic activity indices of 18F-FDG PET are effective predictors of posttransplantation HCC recurrence. In addition to clinicopathologic factors, these indices need to be considered in the selection of candidates for liver transplantation.